МАТЕМАТИКАНЫ ОҚЫТЫЎ ПРОЦЕСИНДЕ ОҚЫЎШЫЛАРДА КРЕАТИВЛИКТИ ҚӘЛИПЛЕСТИРИЎ - Таңирбергенов, С.А.; Сейтмуратов, С.Т. (FAN va JAMIYAT, 2021)
The paper describes an approach for structuring creative lesson of mathematics to enhance its educational effect and achieve interdisciplinary learning outcomes. The authors consider the necessity of education modernization, analyzing the basic approaches to the definition of creativity, suggest introducing creative teaching, aimed at creative abilities development and creative personality formation, the search for the real mechanisms of creative education, into the educational process.